2001
DOI: 10.1046/j.1365-2265.2001.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

TSH‐receptor antibody measurement for differentiation of hyperthyroidism into Graves' disease and multinodular toxic goitre: a comparison of two competitive binding assays

Abstract: H-TRAb diagnosed Graves' disease with a high sensitivity and specificity than P-TRAb. The high occurrence of TRAb in multinodular toxic goitre might in part reflect an overlap between Graves' disease and multinodular toxic goitre in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 35 publications
3
72
0
6
Order By: Relevance
“…Assays used in clinical routine differ considerably in their ability to detect such antibodies (4,5), but recent generations of assays show high sensitivity and specificity (14,15). In the present study, TRAb was measured using a radioreceptor assay that was able to detect TRAb in 83% of the untreated patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Assays used in clinical routine differ considerably in their ability to detect such antibodies (4,5), but recent generations of assays show high sensitivity and specificity (14,15). In the present study, TRAb was measured using a radioreceptor assay that was able to detect TRAb in 83% of the untreated patients.…”
Section: Discussionmentioning
confidence: 92%
“…The number of patients in the three groups (medical/surgical/radioiodine) still included in the analyses is as follows: after 1 year, 48/47/36; after 2 years, 43/44/35; after 3 years, 26/40/35; after 4 years, 24/38/34; and after 5 years, 24/38/34. Serum T 3 , T 4 , and free T 4 were measured as described previously (11). The reference ranges were: T 3 , 1.1-2.5 nmol/l; T 4 , 75-150 nmol/l; and free T 4 , 9-21 pmol/l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conservative handling of data did not alter any of our conclusions: we still found a statistically significant difference in incidence ratio between Aalborg and Copenhagen with regards to MNTG (P!0.001), 'mixed-type' (P!0.001), STA (PZ0.003), and no regional difference in occurrence of GD (PZ0.10). We previously reported that up to 15-20% of hyperthyroid patients with a multinodular scintigraphic pattern are TRAb positive (28). Even higher frequencies of TRAb positivity have been reported in clinic-based studies from Germany (51).…”
Section: Study Strengths and Limitationsmentioning
confidence: 93%
“…GD, Graves' disease; ophthalmopathy (TAO; nZ10) was used as the base for the diagnosis of GD. We considered TRAb as positive above the lower cut-off of the TRAb assays (including borderline positive results), as it was considered so in clinical practice, and it has been shown that either cut-off is highly specific for GD (21). In routine health care, patients were instructed to leave blood samples for white blood cell counts during ATD treatment when they experienced signs of infection.…”
Section: Methodsmentioning
confidence: 99%